2003
DOI: 10.1093/jnci/djg035
|View full text |Cite
|
Sign up to set email alerts
|

Is Patient Travel Distance Associated With Survival on Phase II Clinical Trials in Oncology?

Abstract: Results of phase II curative-intent clinical trials in oncology that are conducted at specialized cancer centers may be confounded by patient travel distance, which captures prognostic significance beyond cancer stage, performance status, and wealth. More work is needed to determine what unmeasured factors travel distance is mediating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
90
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(99 citation statements)
references
References 27 publications
7
90
2
Order By: Relevance
“…Distance was also separately examined as a dichotomous variable, using a conventional cut point (24 km [15 miles]). 15 Census tract poverty rates represent the percentage of residents in the census tract living at or below the 100% poverty line based on 2000 census information. 29 Rurality was examined using the Office of Management and Budget metropolitan classification system and the US Department of Agriculture rural urban classification codes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Distance was also separately examined as a dichotomous variable, using a conventional cut point (24 km [15 miles]). 15 Census tract poverty rates represent the percentage of residents in the census tract living at or below the 100% poverty line based on 2000 census information. 29 Rurality was examined using the Office of Management and Budget metropolitan classification system and the US Department of Agriculture rural urban classification codes.…”
Section: Methodsmentioning
confidence: 99%
“…Although increased travel distance is generally viewed as a barrier to screening, early diagnosis, and treatment, previous studies 15,17,[23][24][25] examining the role of travel distance for patients with cancer have had mixed results. We hypothesize that for patients with melanoma greater distance to a diagnosing provider is associated with increased Breslow thickness or stage at diagnosis.…”
mentioning
confidence: 99%
“…Thus, improving the access of older patients to academic centers may increase their enrollment in clinical trials [Gross et al 2005]. Prior studies have also shown that patients who travel farther to enroll into studies have better outcomes [Lamont et al 2003]. Although this may be partly related to selection of healthier subset of elderly patients, older patients benefit from enrollment in clinical trials of novel agents.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on documenting differences in patient outcomes from administrative or survey data. 5,6 Other studies have focused on changes due to distance traveled, [12][13][14] rural hospital closure, [15][16][17][18][19][20] and staffi ng changes.…”
Section: Discussionmentioning
confidence: 99%